The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 11 12. Shepherd's Pie. 4 1/2 lbs. raw minced Meat. Salt. 9 lbs. Potatoes (freshly cooked and mashed). Parsley (chopped). Gravy. 4 oz. Margarine or Cooking Fat. Method : Cook meat slowly in gravy for 1 hour — see recipe for "Mince and Rice." Line dish with seasoned mashed potatoes. Put in mince and cover with mashed potatoes. Dot with margarine or cooking fat. Bake until brown — approximately 20 minutes. 13. Stoved Potatoes. 4 1/2 lbs. Bacon — rashers. 8 oz. Dripping or Margarine. 9 lbs. Potatoes. 3 pints hot Milk and pot Liquor. 1 lb. Onions — if available. Salt. 4 tablesp. Parsley (chopped). Method : Prepare potatoes and cut into rough pieces. Melt fat, add the peeled sliced onion and rashers of bacon cut into suitably sized pieces and fry gently. Add liquor and potatoes. Simmer gently in covered pan until potatoes are cooked — approximately 30-45 minutes. Turn on to serving dish and sprinkle with finely chopped parsley. 14. Bacon, Rice and Tomatoes. 2 lbs. Rice ; 3/4 lb. Margarine. 4 lbs. boiled Bacon. 4 lbs. Tomatoes (fresh, bottled or canned). Parsley (chopped). Method : Wash rice and cook until soft in boiling salted water — approximately 20 minutes. Strain, mix with tomatoes and margarine and re-heat. Mix with boiled bacon cut into small pieces. Add parsley and serve. VEGETARIAN DISHES. 15. Vegetable and Cheese Hot-pot. 3/4 lb. Dried Peas or Lentils. 2 quarts Milk. 4 1/2 lbs. mixed Vegetables in season. 4 oz. Flour. 4 oz. Fat. 4 1/2 lbs. Potatoes. 12 oz. Cheese (grated). Method : Soak peas or lentils overnight and cook until tender. Prepare vegetables cutting root vegetables into convenient sized pieces. Steam about 3/4 hour. Make sauce with fat, flour and milk. Mix sauce and vegetables. Add cheese and parsley just before serving. 16. Potato and Lentil Pie. 4 lbs. Lentils or Dried Peas. 3/4 lb. Cheese (grated) or lbs. Bacon. 10 lbs. Potatoes. 1 quart Milk. Method : Soak lentils and cook until tender. Boil and mash potatoes. Mash lentils with enough milk to soften. Add bacon (cut into small pieces) or grated cheese. Put in greased dish or tin. Cover with potatoes and brown top in a quick oven. 127/NU/5/5/1/28